Comparison of platelet storage in PL146 and PL732 plastic packs: preliminary in vitro studies. Issue 12 (December 1982) - Edwards, D R; Entwistle, C C
Abstract : This paper is a preliminary report of in vitro studies comparing platelet storage in the new polyolefin PL732 packs with the present polyvinyl PL146 packs. The parameters used to assess platelet viability in these studies were the recovery from the hypotonic stress test (HST) and the pH. The effect of the mass of concentrate was assessed by preparing 20 g, 35 g and 50 g packs. The method of agitation was tested comparing a vertical rotator with a flat-bed, rocking agitator. In all the subgroups the PL732 packs fared better than the PL146 packs in terms of HST recovery and pH. The 35 g and 50 g packs were statistically inseparable but the 20 g packs were significantly worse both in PL732 and PL146. The vertical rotator augmented the beneficial effects of the PL732 plastic especially in terms of pH. The 35 g and 50 g packs in PL732 on a vertical rotator gave results after 5 days storage at 22 degrees C which were vastly superior (p less than or equal to 0.001) to the 35 g and 50 g packs in PL146 after only three days storage. Thus it would appear that the use of PL732 packs might enable the storage life of platelet concentrates to be increased to five days. Further in vivo studies are to be undertaken to ensure these in vitro improvements benefit the patient.